Level of Consumer Trust in Online Store in Purchase of Animal Products during The Covid-19 Pandemic in Padang City - Aditya Alqamal Alianta; Tevina Edwin; Adisti Rastosari; James Hellyward (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2021)
Early in 2020, the world was shocked by the spreading of the Coronavirus from Wuhan China. To mitigate the spread of Covid-19, the Indonesian Government has implemented Large-Scale Social Restrictions (PSBB) throughout Indonesia. PSBB limits the people's movement in Indonesia, including the citizen in Padang city to fulfil their animal protein consumption. The limited movement of the Padang city people has made the citizen begin to purchase animal protein products through online shops. Based on those circumstances, this study aims to measure the level of trust of costumers who fulfil their animal proteins consumption through online stores. The research conducted using a survey method. The respondents were 150 Padang city housewives who were determined by convenience sampling. The research instrument used a questionnaire with a Likert scale. The scores calculated and categorized using a range formula. The results showed that the respondents' trust in the online store was in the high category, with 82.00%. The level of respondents' trust in the urgency of shopping at online stores was in the high category, with a percentage of 73.33%. Level of trust in the reputation and quality of online shop sites was in high category with a percentage of 62.00%. Level of trust in the quality of service provided by online shop sellers was in the high category with a percentage of 70.67%. Level of respondents' trust in making payment transactions is at a high category with a percentage of 84.00%. Level of respondents' in promotions provided by online sellers was in the high category with a percentage of 72.67%. It concluded that a high level of customer trust in the online store will provide satisfaction in purchasing the product, making costumers want to make purchases continuously and turn to be loyal consumers of the online store.